2005
DOI: 10.1109/tasc.2005.848234
|View full text |Cite
|
Sign up to set email alerts
|

AC Losses in Striated YBCO Coated Conductors

Abstract: We measured AC losses in RABiTS nonstriated as well as striated coated conductors provided by the US Air Force Research Laboratory. In addition, samples with different kinds of well defined inter-filament bridging have been measured and their losses compared with those of samples with unbridged filaments and with mono-layer samples. This bridging is designed to aid current sharing between filaments, which is advantageous, but it is necessary to determine if the effect on AC losses is detrimental. It was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 10 publications
(8 reference statements)
2
53
0
Order By: Relevance
“…Drastic improvements in the length and the current carrying capability of HTS-CC have been accomplished for last several years [2][3][4][5][6][7]. The issues in this field is shifting to securing uniformity and reproducibility of the manufacturing processes, improving flux pinning properties (in-field current carrying properties) [8][9][10][11][12][13] and reducing ac (alternate current) losses [14][15][16][17]. When the HTS-CC is used for ac applications, however, the ac-loss of the conductor becomes as important a factor as the high transport current in a high magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Drastic improvements in the length and the current carrying capability of HTS-CC have been accomplished for last several years [2][3][4][5][6][7]. The issues in this field is shifting to securing uniformity and reproducibility of the manufacturing processes, improving flux pinning properties (in-field current carrying properties) [8][9][10][11][12][13] and reducing ac (alternate current) losses [14][15][16][17]. When the HTS-CC is used for ac applications, however, the ac-loss of the conductor becomes as important a factor as the high transport current in a high magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…This is important because it is reported in the literature that the hysteresis losses will be decreased by the inverse of the number of lines (1/N a ) in comparison with a completely covered substrate [15,22]. The currently reported width for patterns is going from 30 µm up to one millimeter when using lithography or etching methods [7,8,12,11,16,19,21,22,24]. With our ink-jet printing technique we can obtain a similar lateral resolution in only one processing step.…”
Section: Discussionmentioning
confidence: 81%
“…These conductors can be wound as coils and, when used in motors and generators instead of copper wires, they can reduce the total size and weight of the device because of their ability to carry high currents without resistance. Yet, these coated conductors produce large losses when used with alternating current (AC) or fields [6][7][8][9]. The high aspect ratio of the coated conductor geometry leads to high hysteresis losses proportional to the width of the superconducting film.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main route to hysteresis (and overall) loss reduction that has been explored in recent years is the replacement of the uniform wide YBCO film with a set of parallel narrow filaments (stripes) [2][3][4][5][6][7][8]. The first experiments have demonstrated that the hysteresis loss in experimental multifilamentary samples can be reduced by at least an order of magnitude.…”
Section: Introductionmentioning
confidence: 99%